Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2013)
This document translates the policy priorities laid out in the Global Policy Agenda (GPA) and the IMFC communique into a work agenda for the Executive Board over the next six to twelve months.